Teaching in Black and White : The Sisters of St. Joseph in the American South - Mattick, Barbara E. (Barbara Elizabeth), 1950- (Book collections on Project MUSE., 2022)
"Teaching in Black and White: The Sisters of St. Joseph in the American South discusses the work of the Sisters of St. Joseph of (the city of) St. Augustine, who came to Florida from France in 1866 to teach newly freed blacks after the Civil War, and remain to this day. It also tells the story of the Sisters of St. Joseph of Georgia, who sprang from the motherhouse in St. Augustine. A significant part of the book is a comparison of the Sisters of St. Josephs' work against that of their major rivals, missionaries from the Protestant American Missionary Association. Using letters the Sisters wrote back to their motherhouse in France, the book provides rare glimpses into the personal and professional lives of these women religious in St. Augustine and other parts of Florida and Georgia, from the mid-nineteenth century through the era of anti-Catholicism in the early twentieth century South. It carries the story through 1922, the end of the pioneer years of the Sisters of St. Josephs' work in Florida, and the end of Sisters of St. Joseph of Georgia's existence as a distinct order. Through the lenses of Catholicism, Florida and Southern history, gender, and race, the book addresses the Protestant concept of domesticity and how it was reinforced in Catholic terms by women who seemingly defied the ideal. It also relates the Sisters' contributions in shaping life in the South during Reconstruction as they established elite academies and free schools, created orphanages, ministered to all during severe yellow fever epidemics, and fought the specter of anti-Catholicism as it crept across the rural regions of the country"--